I.H. Aleksandrov’s activity in the Academy of Sciences of the USSR - Isaienko, O. I. (History of science and technology, 2013)
In the article I.H. Aleksandrov’s participation in the USSR’s Academy of Sciences activity has been highlighted. I.H. Aleksandrov’s being elected as an academician has been grounded as well. His contribution to reforming the Academy and activity in the areas of transport, his role in creating the Soviet Board on productive forces, I.H. Aleksandrov’s guiding a transport commission of Academy have been analyzed in the article.